2006
DOI: 10.1073/pnas.0603085103
|View full text |Cite
|
Sign up to set email alerts
|

An intracellular lamellar–nonlamellar phase transition rationalizes the superior performance of some cationic lipid transfection agents

Abstract: Two cationic phospholipid derivatives with asymmetric hydrocarbon chains were synthesized: ethyl esters of oleoyldecanoylethylphosphatidylcholine (C18:1͞C10-EPC) and stearoyldecanoylethylphosphatidylcholine (C18:0͞C10-EPC). The former was 50 times more effective as a DNA transfection agent (human umbilical artery endothelial cells) than the latter, despite their similar chemical structure and virtually identical lipoplex organization. A likely reason for the superior effectiveness of C18:1͞C10-EPC relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
164
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(171 citation statements)
references
References 53 publications
6
164
1
Order By: Relevance
“…MO-based aggregates induce a relatively low cytotoxicity level, which further reinforces its use as a new helper lipid in this type of non-viral systems. In vivo evaluation of MO-based lipoplexes shall confirm the potential for this neutral surfactant to replace classic helpers in lipofection formulations, although some promising results have already been obtained for other cationic lipid formulations that also form inverted bicontinuous cubic structures [86][87][88]. Ethylphosphatidylcholines are a family of positively charged membrane lipid derivatives that promote the formation of QII G and QII P structures, having been linked to high levels of transfection efficiency with low cytotoxicity in several animal cell lines [89,90], consubstantiating MO's potential role in gene delivery.…”
Section: Role Of Mo As Helper Lipid In Pdna/dodab/mo Lipoplexesmentioning
confidence: 99%
“…MO-based aggregates induce a relatively low cytotoxicity level, which further reinforces its use as a new helper lipid in this type of non-viral systems. In vivo evaluation of MO-based lipoplexes shall confirm the potential for this neutral surfactant to replace classic helpers in lipofection formulations, although some promising results have already been obtained for other cationic lipid formulations that also form inverted bicontinuous cubic structures [86][87][88]. Ethylphosphatidylcholines are a family of positively charged membrane lipid derivatives that promote the formation of QII G and QII P structures, having been linked to high levels of transfection efficiency with low cytotoxicity in several animal cell lines [89,90], consubstantiating MO's potential role in gene delivery.…”
Section: Role Of Mo As Helper Lipid In Pdna/dodab/mo Lipoplexesmentioning
confidence: 99%
“…This is accomplished by efficient compaction and condensation of DNA by the vector for protection against enzymatic degradation, binding of the cationic liposome-DNA complex (lipoplex) to the cellular surface, internalization of the lipoplex within an endosome, and lipoplex fusion with the endosomal membrane for DNA release into the cytosol where the exogenous genetic material can be translocated to the nucleus for expression of the target gene [8], as illustrated in Figure 1. Membrane fusion has garnered particular attention recently through lipid mixing studies highlighting the fusogenic properties of cationic vesicles as critical for successful transfection [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…With increasing N/P ratio, the morphology of the lipoplex transforms from large bead-like structure into smaller particles, wherein DNA molecules are condensed more tightly ( Figures 6C and D). The size of the lipoplexes, whose ζ-potential is positive, is 150-400 nm, is more favorable for cellular uptake via endocytosis (Koynova, Wang & MacDonald, 2006). Given that the lamellar assembly in the lipoplex is responsible for its effectiveness as a gene carrier (Koltover et al, 1998;Koynova, Wang & MacDonald, 2006), the population of active species for gene transfer would increase with increasing in the N/P.…”
Section: Effect Of Bilayer Structure On the Transfection Activitymentioning
confidence: 99%
“…For cationic lipids/DNA complexes (lipoplexes), it has been proposed that a morphological change from lamellar to inverted hexagonal phase in the acidic endosomal environment facilitates the endosomal release and escape of DNA (Bell et al, 2003;Xu & Szoka, 1996). In addition to investigation of intracellular trafficking of polycation-DNA complexes (polyplexes and lipoplexes), observation of morphology and metamorphosis of the complexes is very important to shed light on the mechanism of gene transfer and provide information for development of novel synthetic carriers (Koynova, Wang & MacDonald, 2006;Wan et al, 2008;Tarahovsky, Koynova & MacDonald, 2004). We have reported that polycationic liposomes (PCL) containing cetylated polyethylenimine (cetyl-PEI) possess high gene transfer activity (Yamazaki et al, 2000;Oku et al, 2001;Matsuura et al, 2003).…”
mentioning
confidence: 99%